HABITAT DAN SEBARAN TIKUS BERKANTUNG (Echymipera rufescens) DI PULAU WAMAR KABUPATEN KEPULAUAN ARU - Charolina Larwuy; Maya Marsya Silvia Puttileihalat; Lesly Latupapua (Jurnal Hutan Tropis, 2020)
The purpose of this research was to know thehabitat and distribution of MarsupialRats (Echymipera rufescens) on Wamar Island (Wangel Village, Durjela Village, Gunung Sembilan and Back of Wamar Village)Aru Island District. The method used for Marsupial Rats was the catching of wild animals and then the animals that have been capturedin the mark and back again, while for the catching of Marsupial Rats was a tool used is a trap.Analysis of distribution of Marsupial Ratsusing Morista Index while to know the habitat of Marsupial Rats using Line Intercept (line transect) method and the printed path from the analysis to know the pattern of distributionused Morista Index. The result of the research showed that the awareness of the pattern analysis of the Marsupial Rats distribution to the four locations including Wangel Village, Durjela Village, Gunung Sembilan and Back of Wamar Village, from the pattern of horizontal distribution of Marsupial Rats that was the same as random with the index values were Wangel Village was 0.067, Durjela Village was 0.067, Gunung Sembilan village was 0,000, and Back of Wamar village was 0,000. So the pattern of distribution on Wamar Island was random with index value of 0.079. Habitat from the Marsupial Rats own were secondary dryland forest and mixed with shrubs which was his habitat while the feed frm the Marsupial Rats was Galoba, Calladium, Sweet Potato, and Bananas.